AN ANALYSIS OF FIGURATIVE LANGUAGES USED IN SIMPLE PLAN'S SONG LYRICS IN THE ALBUM ENTITLED "GET YOUR HEART ON!" - ., Ni Made Yudi Harsini; ., Prof. Dr.I Ketut Seken,MA; ., Dewa Ayu Eka Agustini, S.Pd., M.S. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini bertujuan untuk menemukan macam-macam majas yang digunakan dalam lirik lagu Simple Plan dan makna yang tersirat berdasarkan penggunaan majas dalam lirik-lirik lagu tersebut. Untuk mengaplikasikan penelitian ini, 13 lagu dalam album Simple Plan yang berjudul “Get Your Heart On!” telah dipilih untuk dianalisis menggunakan teori oleh Laurence Perrine (1982). Rancangan penelitian deskriptif dengan pendekatan kualitatif diimplementasikan dalam penelitian ini. Penelitian ini menunjukkan bahwa: (1) terdapat sembilan macam majas yang dipergunakan dalam lirik-lirik lagu Simple Plan dalam album mereka yang berjudul “Get Your Heart On!”, yaitu: Metaphor, Simile, Personification, Overstatement/ Hyperbole, Understatement, Metonymy, Paradox, Symbol dan Verbal Irony; (2) makna yang tersirat dalam penggunaan majas dalam lirik-lirik tersebut sebagian besar berkaitan dengan makna konotatif.Kata Kunci : Majas, Lirik-lirik Lagu, Makna Tersirat. This study aimed to find out the kinds of figurative language used in Simple Plan’s song lyrics and the meaning implied based on the use of figurative language in those lyrics. To administer this study, 13 songs in Simple Plan’s album entitled “Get Your Heart On!” were selected to be analyzed by using Laurence Perrine’s theory (1982). Descriptive design within qualitative approach was implemented in this study. This study reveals: (1) there are nine kinds of figurative language are used in Simple Plan’s song lyrics in their album entitled “Get Your Heart On!”, such as: Metaphor, Simile, Personification, Overstatement/ Hyperbole, Understatement, Metonymy, Paradox, Symbol, and Verbal Irony; (2) the meaning implied based on the use of figurative language in those lyrics mostly deal with connotative meaning.keyword : Figurative Language, Song Lyrics, Meaning Implied.